The Impact of Social Media and 4C Skills (Critical Thinking, Communication, Creativity, Collaboration) in English Language Learning: Students’ voices - Juni, Muliana; Mahmud, Muzdalifah; Machmud, Karmila (English Education Department at FKIP Nommensen University, 2025)
This study explores students’ subjective perspectives on the use of social media platforms (e.g., TikTok, Instagram, YouTube) in developing their 21st-century 4C skills (Critical Thinking, Communication, Creativity, Collaboration) within an English Language Learning (ELL) context. Using descriptive qualitative methods with semi-structured interviews, this study synthesizes wide-ranging perceptions on the use of platforms and how they facilitate students in improving 4C skills in English learning. The results were further analyzed thematically. Key findings indicate that, although students recognized that social media is an accessible and engaging tool for English learning, its use for developing 4C skills is not without significant challenges. Students posited that social media effectively facilitates the practice of communication skills (writing and speaking), stimulates creativity, and supports online collaboration skills. However, they also suggested that the development of critical thinking is hampered by the difficulties in evaluating the credibility of information online. The practical implications of this study highlight the need for lecturers to design structured pedagogical support and for policymakers to integrate digital literacy into the curriculum. Without strategic guidance, the potential of social media to enhance 4C skills is at risk of being underutilized.